Design of Digital Framework for Regional Education Supervision based on Cloud Computing - Lixia Wu, Yanshen Liu (Forest Chemicals Review, 1970)
With the rapid development of cloud computing and other emerging information technologies, the pace of informatization in the education industry is also accelerating. The modernization and digitalization of educational supervision are also facing new opportunities and challenges. Based on the analysis of the current digital deficiencies in the implementation of educational supervision and the advantages of cloud computing, this paper proposes a hierarchical framework for the digitalization of educational supervision, and elaborates on the hierarchical functions and characteristics of the framework in order to serve as educational supervision. Provide reference for digitalization and modernization.